Integrating Waterped Technology Into Learning: Advancing Elementary Students’ Reading Comprehension Abilities - Moh. Wardi Moh. Wardi; Ismail Ismail; Supandi Supandi; Hodairiyah Hodairiyah (Jurnal Ilmiah Sekolah Dasar, 2025)
Reading comprehension remains a critical challenge in primary education worldwide, with many students struggling to grasp and analyze written texts effectively due to the lack of engaging and adaptive learning tools. Despite advancements in educational technology, there is a noticeable gap in the development of innovative, technology-based media specifically tailored to enhance literacy skills among young learners, particularly in fostering deeper comprehension abilities. This study aims to produce technology-based waterped media and to determine the effectiveness of the media in improving reading comprehension skills. Research and development refers to the steps developed by Borg and Gall. The subjects of the field trials involved 34 students and two grade V teachers. This study's data collection techniques and instruments used were questionnaires, scales (media validation and material validation), and tests. The data analysis technique in this study is divided into several stages, including preliminary study data analysis, data analysis in the media development process, feasibility and effectiveness of media developed through trial results. The study showed that technology-based waterped media could improve reading comprehension skills in the "very good" category. The effectiveness of the technology-based waterped press can be seen from the test results using the independent sample t-test, which shows a significance value of 0.501 or a sig value> 0.05 so that there is a significant difference between the results of reading comprehension skills between the control and experimental classes before and after using technology-based watered media.